The CPM Platinum yearbook 2007 (Wiley, 2007)
This invaluable resource contains a wealth of information for investors and traders who need to make fully informed investment decisions with regard to these commodities. Topics discussed range from the supply and demand fundamentals of platinum, palladium, and rhodium to emerging trading and investment opportunities for these PGMs. Filled with in-depth insight and proven advice, The CPM Platinum Group Metals Yearbook 2007 contains all the information you need to succeed in the platinum, palladium, and rhodium markets.